ANALISIS PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN SELF EFFICACY MELALUI KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DINAS KOPERASI DAN USAHA MIKRO KOTA SURABAYA - Linna Fitri Murtiningsih; Wasis Budiarto; Mei Indrawati (Jurnal Manajerial Bisnis, 2017)
Human resource management in the regional apparatus organization (OPD) plays a role in managing human resources as the subject of policy and activity implementers. The success of an organization to achieve its best performance level is influenced by leadership style. High employee satisfaction supports the smooth working process. Organizational culture has a significant impact on long-term performance. Self efficacy improves job satisfaction and employee performance. The type of research is a statement using a questionnaire as a tool to retrieve data. Using exsplanatory research with sample of 93 employees through path analysis method. Based on the results of model analysis, the empirical casual relationship between leadership style, organizational culture, self efficacy and job satisfaction have a significant effect on employee performance at the Department of Cooperatives and Micro Enterprises Surabaya.